Socioeconomics Indicators of Microfinance Borrowers in Sarawak - Ian Gerard, Umpang; Rossazana, Ab Rahim (Human Resource Management Academic Research Society, 2025)
Microfinance has been recognized as a vital instrument for poverty alleviation, particularly in contexts where access to formal financial institutions is limited. In Sarawak, Malaysia, agencies such as TEKUN Nasional have expanded outreach to marginalized households, yet questions remain regarding the extent to which these programs improve borrowers’ socioeconomic well-being. This study investigates the relationship between microfinance services namely loans, non-financial support, access to financing, and repayment and six socioeconomic indicators: income, savings, consumption, healthcare, education, and employment. The results show that microfinance contributes positively to healthcare, savings, and education, while its effects on income, employment, and consumption are less consistent. Furthermore, repayment challenges and unequal access highlight structural limitations that constrain the transformative role of microfinance. These findings suggest that while microfinance provides important opportunities for livelihood improvement, it cannot fully address poverty in isolation. Integrating financial services with training, financial literacy, and supportive monitoring mechanisms is essential for enhancing long-term socioeconomic outcomes and reducing persistent poverty in Sarawak.